Prognosis of Asymptomatic Carotid Artery Occlusion: Systematic Review and Meta-Analysis. Issue 5 (May 2016) - Hackam, Daniel G.
Abstract : Background and Purpose—: The aim of this systematic review was to quantify the risk of ipsilateral stroke in patients with asymptomatic carotid artery occlusion (ACAO). Methods—: Studies reporting ipsilateral stroke risk in ACAO were identified by a search of MEDLINE, EMBASE, and study bibliographies. Study estimates were pooled using a random effects model, and heterogeneity was quantified using the I 2 statistic. The primary outcome was the annual rate of ipsilateral stroke. Results—: Thirteen studies were identified, encompassing 718 patients with ACAO who were followed up for a median of 2.8 years. The annual rate of ipsilateral stroke was 1.3% (95% confidence interval, 0.4–2.1; I 2 =53%). The annual rate of ipsilateral transient ischemic attack was 1.0% (95% confidence interval, 0.3–1.8; I 2 =40%). The annual rate of death was substantially higher at 7.7% (95% confidence interval, 4.3–11.2; I 2 =83%). Correction for possible publication bias for the primary outcome suggested a lower risk of ipsilateral stroke (0.3% per year; 95% confidence interval, –0.4 to 1.1). Conclusions—: Stroke in ACAO is relatively infrequent, but patients face high mortality rates. This suggests the need for intensified medical therapy in ACAO. Abstract : Supplemental Digital Content is available in the text.